Usulan Strategi Pemasaran untuk Meningkatkan Keputusan Pembelian Kersen Patisserie - Wardi, Putri Amalia; Ramdani, Rizal (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Current business developments require business owner to pay more attention to their business strategies and administration such as product quality and marketing by paying attention to consumer desires because of similar competing products requires companies to make their products more attractive compared to competing products. The food industry, type of business that continues to grow, such as cookies and dessert businesses. This study aims to determine a more effective marketing strategy to increasing sales at Kersen Patisserie. This study consists of 3 (three) independent variables, namely business administration, marketing, and relationship marketing, and the dependent variable is purchasing decisions. The population of this study is Kersen Patisserie consumers. The data used are primary data obtained from 100 respondent samples. The data processed in this study used multiple linear regression analysis. Based on the results of statistical data analysis, the indicators in this study are valid and reliable variables. In the classical assumption test, there is no multicollinearity, and the data is normally distributed. The results of this study indicate that partially the marketing and relationship marketing variables have a significant effect on purchasing decisions. On the other hand, business administration partially does not affect purchasing decisions. Based on simultaneous results, it is proven that the business administration, marketing, and relationship marketing variables have a significant effect on purchasing decisions.